Nitrifier Gene Abundance and Diversity in Sediments Impacted by Acid Mine Drainage - Ramanathan, Bhargavi; Boddicker, Andrew M.; Roane, Timberley M.; Mosier, Annika C. (Frontiers in Microbiology, 2017)
Extremely acidic and metal-rich acid mine drainage (AMD) waters can have severe toxicological effects on aquatic ecosystems. AMD has been shown to completely halt nitrification, which plays an important role in transferring nitrogen to higher organisms and in mitigating nitrogen pollution. We evaluated the gene abundance and diversity of nitrifying microbes in AMD-impacted sediments: ammonia-oxidizing archaea (AOA), ammonia-oxidizing bacteria (AOB), and nitrite-oxidizing bacteria (NOB). Samples were collected from the Iron Springs Mining District (Ophir, Colorado, USA) during early and late summer in 2013 and 2014. Many of the sites were characterized by low pH (<5) and high metal concentrations. Sequence analyses revealed AOA genes related to Nitrososphaera, Nitrosotalea, and Nitrosoarchaeum; AOB genes related to Nitrosomonas and Nitrosospira; and NOB genes related to Nitrospira. The overall abundance of AOA, AOB and NOB was examined using quantitative PCR (qPCR) amplification of the amoA and nxrB functional genes and 16S rRNA genes. Gene copy numbers ranged from 3.2 x 104 - 4.9 x 107 archaeal amoA copies * µg DNA-1, 1.5 x 103 - 5.3 x 105 AOB 16S rRNA copies * µg DNA-1, and 1.3 x 106 - 7.7 x 107 Nitrospira nxrB copies * µg DNA-1. Overall, Nitrospira nxrB genes were found to be more abundant than AOB 16S rRNA and archaeal amoA genes in most of the sample sites across 2013 and 2014. AOB 16S rRNA and Nitrospira nxrB genes were quantified in sediments with pH as low as 3.2, and AOA amoA genes were quantified in sediments as low as 3.5. Though pH varied across all sites (pH 3.2-8.3), pH was not strongly correlated to the overall community structure or relative abundance of individual OTUs for any gene (based on CCA and Spearman correlations). pH was positivity correlated to the total abundance (qPCR) of AOB 16S rRNA genes, but not for any other genes. Metals were not correlated to the overall nitrifier community composition or abundance, but were correlated to the relative abundances of several individual OTUs. These findings extend our understanding of the distribution of nitrifying microbes in AMD-impacted systems and provide a platform for further research.